The Role of Regulatory Myeloid Cell Therapy in Renal Allograft Rejection - Zhuang, Jingming; Hou, Jiangang (Frontiers in Immunology, 2021)
Kidney transplantation has always been a primary therapy for end-stage renal disease (ESRD). But this does not mean that we have fully unraveling the mystery of kidney transplantation and can make each patient get a favorable prognosis. Immune rejection has always been a stumbling block when we try to increase the success rate of kidney transplantation and improve the long-term outcomes. The acute rejection is highly prevalent, but the immune response mediated by chronically activated antibodies will trigger chronic rejection and ultimately lead to graft failure. At present, immunosuppressive (IS) agent prepared chemically is mainly used to prevent the acute or chronic rejection, but it has failed to increase the long-term allografts survival or reduce conversions of acute to chronic rejection and is accompanied by many adverse reactions. Therefore, many studies have begun to use immune cells to regulate the immune response in order to control allograft rejection. This article will focus on the latest study and prospects of more popular regulatory myeloid cells in the direction of renal transplantation immunotherapy and their relationship with other regulatory cells.